Selling professional and financial services handbook - Paczosa, Scott; Peruchini, Chuck (Hoboken, New Jersey : John Wiley & Sons, Inc., 2013)
"Times are tough for people who sell financial services and this book offers a new solution proven in practice. The book describes methods the authors have used and taught since the 1990s, most recently at a major consulting firm, where they led a national sales team to revenue gains of 500% over four years -- in a period that included the recession of 2008-2010. Their book shows how the same approach can grow sales for public financial service firms struggling to sell to corporate and institutional clients in today's tight economy. The solution is not any new twist on face-to-face selling techniques or the art of persuasion. It's a strategic approach built around a simple fact: the markets are tight but far from static. Even with lean budgets, client companies must respond to urgent changes and emerging threats in their industries. Thus they will buy services from the sellers who can help them detect, understand, and cope with what's coming their way. The book outlines a systematic way of becoming such a valued resource. Readers learn to scan the horizon for early signs of "rock-ripple events." Major changes in the business world often spring from new developments that are little noted or heeded, at first, by the client companies soon to be affected by them. But like a rock dropped in a pond, these events set off ripples that sweep through entire industry sectors, creating must-have service needs"--
ROUNDTABLES AND OTHER "SCALE" OUTREACH EVENTSKEEP IT SIMPLE; EXTENDING RELATIONSHIPS INTO OTHER INITIATIVES; THE MULTIPLIER EFFECT AND THE SMALL-WORLD EFFECT; INDIRECT SALES: THE ULTIMATE PAYOFF; Chapter 12: Hunting or Farming? It's Both: An Approach for New and Existing Clients; THE DOWNSIDES OF ACCOUNT-CENTRIC FARMING (AND WHY ROCK-RIPPLE IS SUPERIOR); EFFICIENCIES ON THE HUNTING SIDE; WHERE THE DIFFERENCES COME IN; INDIRECT SALES: THE BIG DIFFERENCE; Chapter 13: Where to Go from Here; BOARDING CALL: THE DESTINATION, THE TICKET; IT ALWAYS STARTS WITH WHAT'S NEXT
Includes index.
Print version record and CIP data provided by publisher.
Keywords: Financial services industry; Strategic planning; Selling; BUSINESS & ECONOMICS -- Finance; Financial services industry; Selling; Strategic planning; Electronic books